2021
DOI: 10.3390/ijms22063211
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA CRYBG3 Promotes Lung Cancer Metastasis via Activating the eEF1A1/MDM2/MTBP Axis

Abstract: The occurrence of distant tumor metastases is a major barrier in non-small cell lung cancer (NSCLC) therapy, and seriously affects clinical treatment and patient prognosis. Recently, long non-coding RNAs (lncRNAs) have been demonstrated to be crucial regulators of metastasis in lung cancer. The aim of this study was to reveal the underlying mechanisms of a novel lncRNA LNC CRYBG3 in regulating NSCLC metastasis. Experimental results showed that LNC CRYBG3 was upregulated in NSCLC cells compared with normal tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
(42 reference statements)
0
9
0
Order By: Relevance
“…It had been confirmed in previous studies that EEF1A1 made oncogenic functions in various tumors, such as lung cancer [ 20 ], renal cell carcinoma [ 21 ], hepatocellular carcinoma [ 22 ], and GC [ 23 , 24 ], etc. Besides, EEF1A1 expression level is associated with poor prognosis in GC based on the Cancer Genome Atlas (TCGA) database (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 78%
“…It had been confirmed in previous studies that EEF1A1 made oncogenic functions in various tumors, such as lung cancer [ 20 ], renal cell carcinoma [ 21 ], hepatocellular carcinoma [ 22 ], and GC [ 23 , 24 ], etc. Besides, EEF1A1 expression level is associated with poor prognosis in GC based on the Cancer Genome Atlas (TCGA) database (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 78%
“… 13 , 34 For instance, Wu A. et al found that eEF1A1 could directly target the promoter region of murine double minute 2 to regulate the expression and promote lung cancer metastasis. 36 In this study, the WGCNA algorithm was used to discover the core genes. The method of using the WGCNA algorithm to discover the core genes by screening clinical feature‐related gene co‐expression networks is well‐established.…”
Section: Discussionmentioning
confidence: 99%
“…The Ion 318 ™ Chip v2 BC chip used in this study can sequence 96 samples at a time. It can not only provide new research methods for methylation-related research, but also provides new ideas for the epigenetic-related research (67)(68)(69)(70).…”
Section: Discussionmentioning
confidence: 99%